Analisis Sentimen Komentar Video Putusan MA Terkait Kaesang Menggunakan Metode Naive Bayes - Abim Febri Hananto; Raihan Canggih Panilih; Reihan Setya Banda Syah Putra; Tariq Tariq; Wildan Setiawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Political dynasty is a political power exercised by a group of people who are related by family, with the aim of obtaining power and ensuring that this power remains within the group by passing it on to other family members. This study conducts a sentiment analysis on comments related to the Supreme Court decision which is believed to pave the way for Kaesang Pangarep in support of Jokowi's political dynasty. Sentiment analysis is carried out using the Naive Bayes method, a commonly used algorithm for text classification based on probability. The data used consists of comments from videos taken from social media platforms. These comments are then categorized into positive, negative, and neutral sentiments. The results of the study show the distribution of public sentiment towards this issue, providing an overview of how the public responds to the decision. The Naive Bayes method is chosen for its simplicity and its ability to provide reasonably accurate results in text analysis.